COMPARISON OF E-ASSESSMENT SYSTEMS MAPLE T.A. AND WEBWORK - Jahodová Berková, Andrea; Matoušová, Ivana (International Association of Technology, Education and Development (IATED), 2018)
The paper focuses on the possibilities and limits of using the e-assessment systems Maple T.A. and WebWork. Comparison of these systems is introduced through experiences of users (lecturers and students). The primary difference between e-assessment systems is, of course, the financial side (commercial versus open source software). Another distingtive point of view is the input of mathematical symbols and operationing with them (via system Maple and Equation editor or Pearl parser and text string) and the complexity of creating and programming questions using templates with MathML or LaTeX syntax. Very important aspect for users is also well-arranged library of questions. Since there is a lack of prepared questions in the Czech language or any link with Czech textbooks publishers, it is very unpleasant for lecturers in the Czech environment to have a poor structuring database of questions. Opinions of lecturers who have experience with e-assessment systems emerging from the interviews are included in this paper. Additionally, the core of the paper lies in students' opinions and attitudes to e-assessment systems arising from the focus group with students who had the opportunity to try both systems.
Porovnání e-assesment systémů Maple T.A. a WeBWork
Keywords: mathematics education; matematické vzdělávání; assesment in mathematics; e-assesment; maple t.a.; webwork; online hodnocení; maple t. a.; webwork